2017
DOI: 10.1002/stc.2126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of structural faults in piers of masonry arch bridges through automated processing of laser scanning data

Abstract: Summary This paper introduces a new methodology for the automated processing of large point clouds for the diagnosis of structural pathologies in piers of masonry arch bridges. This method starts with the automatic segmentation of the global point cloud of the entire bridge in its different structural elements (piers, arches, spandrel walls, etc.). Later, piers were further segmented in order to be able to detect and quantify structural pathologies. Particularly, faults are based in geometric anomalies (tilts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…12). This reconstruction matches the geometry of the bridge and would enable the application of automatic segmentation algorithms of the bridge parts [27,28], not being affected by the lack of data due to the damage of the structure. Geometrically, the reconstruction matches the dimensions of the cutwater, although at masonry level, the stones do not match exactly.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…12). This reconstruction matches the geometry of the bridge and would enable the application of automatic segmentation algorithms of the bridge parts [27,28], not being affected by the lack of data due to the damage of the structure. Geometrically, the reconstruction matches the dimensions of the cutwater, although at masonry level, the stones do not match exactly.…”
Section: Resultsmentioning
confidence: 91%
“…Later on, Riveiro et al developed a methodology for automatically segmenting their structural elements [27]. Concerning the inspection of masonry arch bridges, Sánchez-Rodríguez et al showed an automatic processing method for laser scanning data in order to detect faults in their piers [28]. Once the piers were isolated from the bridge, the azimuth and elevation angles of each face were evaluated.…”
Section: Related Workmentioning
confidence: 99%
“…Calculations for determining behavior provide the basic information needed to select restoration, repair and strengthening techniques suitable for historical buildings. The existing methods used to perform the analyzes have several advantages and disadvantages depending on the approaches and assumptions used [15][16][17]. In historical buildings, it is necessary to interpret the behavior occurring accurately and precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Law et al 21 used TLS data to identify and quantify the concrete loss of a structure with ongoing deterioration. A laser scan‐based automated inspection method was developed for determining the structural faults of piers in masonry arch bridges 22 . Zeibak‐Shini et al 23 used laser scan data for generating an initial “best‐guess” for the new locations of the façade structural members and then used the extracted information for a recursive process in which the location and damage to each object is refined.…”
Section: Introductionmentioning
confidence: 99%